Pengaruh Pengenaan Pajak atas BKP dan JKP terhadap Barang Impor dan Platform Digital dalam Ekonomi Indonesia - Jasmine Septiani; Siti Khairunnisa; Rudi Sanjaya; Ryan Hadi Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of taxation on Taxable Goods (Barang Kena Pajak/BKP) and Taxable Services (Jasa Kena Pajak/JKP) on imported goods and foreign digital platforms in Indonesia’s economic activities. The research was conducted using a qualitative descriptive approach through a literature review of tax regulations, scientific journals, books, and other relevant secondary data sources. The findings indicate that the imposition of Value Added Tax (VAT) on imported goods contributes to increasing state revenue and regulating the flow of imported products, while also encouraging consumers to consider domestic products due to higher import costs. Meanwhile, the implementation of VAT on foreign digital services through the Electronic Commerce (PMSE) scheme has expanded the tax base in the digital economy, increased government revenue, and promoted fair competition between foreign digital companies and domestic businesses. The study also reveals that taxation serves not only as a budgetary instrument but also as a regulatory tool that influences consumption patterns, market balance, and economic behavior. Therefore, the taxation of BKP and JKP plays an important role in supporting sustainable economic growth, strengthening fiscal capacity, protecting domestic industries, and adapting the Indonesian tax system to the challenges of globalization and digital transformation.